Determination of Antioxidant Activity and Phenolic Compounds of Methanolic Extract of Java Plum (Syzygium cumini Linn. (Skeel) Seed - Rohadi Rohadi; Umar Santoso; Sri Raharjo; Iip Izul Falah (Indonesian Association of Food Technologists, 2017)
Methanolic extract of Java Plum (Syzygium cumini L. (Skeel) seed (MEJS) is potential source of natural antioxidant. As indicated by several in vitro measurements, the extract had strong DPPH (1,1 diphenyl, 2–picryl hydrazyl) and ABTS (2,2-azinobis, 3-ethylbenzothiazoline-6-sulphonate) radical scavenging activity, strong Ferric Reducing Antioxidant Power (FRAP) and moderate inhibition activity of linoleic acid oxidation. This study aimed to determine antioxidant activity and phenolic compound of Java Plum seed (Syzygium cumini L. (Skeel) methanolic extract fractions. Phenolics compound identification using Thin Layer Chromatography (TLC) showed that all fractions (polar, semi polar and hydrolyzed semi polar fraction) contained Gallic acid, Tannic acid and flavonol’s Rutin. HPLC-DAD analysis showed that its polar fraction contained 25 ppm flavonol’s Quercetine and 55181 ppm flavonol’s (+)- Catechin, ethyl acetate fraction contained 54 ppm flavonol’s Rutin and 528 ppm (+)- Catechine, while hydrolyzed ethyl acetate fraction contained 404 ppm Rutin and 28692 ppm (+)- Catechine.